ANALISIS MANFAAT RESTORASI GAMBUT BERBASIS AGROFORESTRI SAWIT DI DESA TANJUNG BERINGIN KECAMATAN TANJUNG LUBUK KABUPATEN OGAN KOMERING ILIR - Dimas Haidar Ramadhan; Desi Aryani; Yulian Junaidi (Jurusan Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Mataram, 2025)
Indonesia is country with the largest tropical peatland in the world with scale ​​24.7 Ha forms a peat hydrological unit. Sumatra is the second province with the largest peatland area in Indonesia at 2.09 Ha. Ogan Komering Ilir Regency has the largest peat in South Sumatra with an area of ​​1.03 Ha. Exploitation and land management not suitable with the characteristics of peatland cause recurring fires every year and damage the function of the peat ecosystem. The activity of restoring peatland with agroforestry commodities that are adaptive and have high economic value on peatland is one of the strategic objectives to protect the environment and increase community income. Data collection was carried out in September 2025. The method used was the survey method. Determination of the number of samples used the census method by taking a population of 8 farmers who manage their land with oil palm agroforestry. The analysis was conducted using four financial feasibility indicators. The results of this study: Peat restoration based on oil palm agroforestry is feasible with an NPV value of 360.912.289, an IRR of 42%; Net B/C of 5.0, and a Payback Period of 2.4 years.